A study on the double-edged sword effect of inclusive leadership on employees’ work behaviour—dual path perspective of cognition and affection - Chen, Hao; Bao, Jiaying; Wang, Liang; Zhang, Zihan (Frontiers in Psychology, 2024)
In order to cope with the volatile social environment and organisational change, more and more scholars call on leaders to stimulate subordinate effectiveness to a greater extent with inclusive behaviour. Existing studies focus on the positive impact of inclusive leadership, but ignore its potential negative impact. This study integrates Cognition-affection Personality System Theory to explore the double-edged sword mechanism of inclusive leadership on subordinates’ work behaviour. Through the data analysis of 518 paired questionnaires collected in three stages, the results are as follows: Inclusive leadership has a positive impact on subordinates’ psychological entitlement and state gratitude; Psychological entitlement and state gratitude play mediation roles not only between inclusive leadership and work withdrawal behaviour, but also between inclusive leadership and active behaviour; Subordinate narcissistic personality moderates the positive effect of inclusive leadership on psychological entitlement and state gratitude, and then moderates the indirect effect of inclusive leadership on subordinate work withdrawal behaviour and proactive behaviour through psychological entitlement and state gratitude. The above results expand the research on the action mechanism and boundary conditions of inclusive leadership in Chinese organisational context, and provide practical guidance for organisational managers to effectively conduct inclusive leadership.